A Strategic Operations Management Framework for Enhancing Service Efficiency, Therapist Productivity, and Patient Flow Optimization in Outpatient Physical Therapy Clinics - Dhirenbhai Kalal (The Eastasouth Management and Business, 2024)
Outpatient Physical Therapy (OPT) clinics are facing increasing pressure to balance patient demand, strict therapist staffing levels, patient non-attendance and productivity demands dictated by reimbursement requirements. This paper brings together results from twenty peer-reviewed and thesis-level papers covering healthcare scheduling optimization, physical therapist productivity measurement, patient no-show prediction, and lean process redesign to present an integrated Strategic Operations Management Framework for outpatient physical therapy environments. It combines a predictive scheduling optimization system with a real-time capacity allocation system for therapists and a lean-based patient-flow monitoring loop, based on the evidence gained from a discrete-event simulation and mathematical programming. Synthesized results show that a simulation-optimization scheduling approach can increase therapist utilisation to around 91 per cent and decrease the incidence of no shows up to 27 per cent over rule-based block scheduling, and lean healthcare interventions can lead to a median decrease in patient waiting time by 31 per cent and process cycle time by 26 per cent. Productivity indices that have been created over the past 40 years from departmental evaluations reveal a cumulative increase of about 58 percent, while documented risks of clinician burnout have occurred when trying to increase productivity without workforce protections. This proposed framework is divided into four interacting zones: predictive scheduling, lean process redesign, dynamic capacity management and workforce well-being, and provides a staged implementation roadmap. Limitations associated with the retrospective and cross setting nature of the synthesized evidence are discussed, as are implications for clinic administrators, payers, and workforce policy.